PRODUKSI DAN KARAKTERISASI BIODIESEL BERBAHAN BAKU MINYAK JELANTAH - Ardi Kurniawan Makalalag; Doly Prima Silaban (Balai Riset Dan Standardisasi Industri Manado, 2020)
Biodiesel is an alternative fuel that produced from renewable material alkyl esthers and fatty acids. This research aimed to characterize biodiesel production from used cooking oil. This research method was mixing used cooking oil and methanol with molecule weight ratio (1:4; 1:6; 1:8) by using KOH 0.75% as catalyst. Reaction temperature were (oC) 50, 60 and 70 at 80 minutes reaction time. Next, top layer was heated at 50oC for 30 minutes. Density, viscosity, acid value and yield of biodiesel were observed. Data obtained from testing result were analyzed descriptively. Biodiesel density value were (kg/m3) 898-1095; viscosity were (cSt) 6,4-8,6; Acid value were (mg KOH/g) 0,6-1,1 with biodiesel yield were (%) 76,2-81,6.Keywords: biodiesel, used cooking oil, KOH